The faithfuls’ rights as expression of values - FABRIS, COSTANTINO-M. (Prawo Kanoniczne, 2014)
This article offers a broad analysis on the theme relevant to the canonical subject “The People of God”. It provides particularly insight into the theme of the rights of the faithful within the ecclesiastical framework, with special emphasis on the rights of the lay faithful. The discussion regarding the recognition of the rights of the faithful and those of the laity, has indeed characterized canonical scholarship since the nineteenth century, influencing also the innovations of the second Vatican Council. All the theme of the rights is focused in an optics of “rights as values”. The author provides also a panoramic overview of the relevant canonical literature, making reference to the innovations introduced in the course of time by subsequent juridical reforms.